Exploring Cu(triNHC) as a Bifunctional Catalyst for Carbonate Synthesis From CO2 and Epoxy Amines/Sulfides/Ethers - Ha, Changsu; Lee, Jong Hyeok; Sokolova, Ekaterina; Sung, Kihyuk; Jang, Hye Young (Applied Organometallic Chemistry, 2025)
This study highlights the synergistic interplay between a Lewis acidic copper ion and a dissociated ligand from Cu(triNHC) complexes in the synthesis of cyclic carbonates from CO2 and epoxy compounds. The reactions were found to proceed efficiently under Cu(triNHC)-catalyzed conditions, yielding significant quantities of cyclic carbonates across various epoxy substrates encompassing amine, sulfide, and ether functionalities. Stereochemical analyses underscore a pronounced propensity for retaining the stereochemistry of epoxy compounds in the resultant carbonates. This suggests a mechanism involving double inversion of stereochemistry during the reaction, which comprises catalyst-mediated epoxide ring opening, subsequent CO2 addition, and carbonate ring closing. These findings align with established mechanisms for CO2 fixation reactions, shedding light on the intricate pathways underlying this catalytic process.
Keywords: Bifunctional catalysts; Condition; Copper ions; Cu(trinhc); Cyclic carbonates; Epoxy; Epoxy amine; Epoxy compound; Lewis acidic; Synthesis of cyclic carbonates; bifunctional catalyst; carbon dioxide; carbonates; Cu(triNHC); epoxy amines